Causes of death in children younger than 5 years in China in 2008 – Authors' reply - Rudan, Igor; Chan, Kit Yee; Zhang, Jian Shayne F; Theodoratou, Evropi; Guo, Yan; Campbell, Harry (The Lancet (British edition), 2010)
[...] we believe that the estimates of proportional causes of death in our paper should be considered reliable and that the rapid decline in pneumonia mortality in China can be largely explained by a rapid decline in the overall mortality rate in children younger than 5 years. China has addressed child mortality through careful central planning and the coordinated, massive improvement in social determinants of child survival, near-universal primary health care, expanded vaccination coverage, economic growth, infrastructure development, health-systems building, integration of minority populations, maternal education, improved sanitation, and the introduction of the "one child" policy.